Evaluation of radiographic pulmonary artery diameter and echocardiographic pulmonary artery pressure in COPD patients in South-West Nigeria - Zuliat A. Awoyemi; Faosat O. Jinadu; Abimbola O. Fasan-Odunsi; Abiola O. Adekoya; Olayinka O. Adeyeye; Folasade A. Daniel (Lung India)
Background and Objective: Cardiac comorbidity is an important prognostic factor in chronic lung diseases. The presence of pulmonary hypertension (PH) in chronic obstructive pulmonary disease (COPD) is associated with higher morbidity and mortality, with an increased risk of exacerbations, compared with COPD patients without PH. Methods: One hundred and twenty patients with COPD and sex and age-matched 120 non-COPD patients were enrolled. A mean right descending pulmonary artery diameter (RDPAD) on chest radiographs (CXR), mean pulmonary arterial pressure (mPAP) on echocardiograms, and lung function on Spirometry were evaluated. Student t-test, Chi-square, and ANOVA were used to test these two groups‘ differences to determine PH. The Spearman correlation coefficient assessed the linear relationship between the mPAP and RDPAD, and the statistical significance was P < 0.05. Results: The subjects’ mean RDPAD was higher than the controls, 15.48 ± 1.64 mm vs. 14.23 ± 1.44 mm (P value < 0.001), and higher in men than in women. The subjects’ mean RDPAD significantly increased with the severity of COPD (P = 0.007) and increasing body mass index (BMI) (P = 0.032). The subjects’ median mPAP was higher than the controls (U = -5.490, P < 0.001), with higher values in the women. A significant correlation was found between the RDPAD on CXR and the mPAP from echocardiograms (r = 0.263, P < 0.001), with a PH prediction accuracy of 81%. Conclusion: The study demonstrated that RDPAD on the CXR significantly correlates with echocardiography-estimated mPAP, and they are diagnostic tools good enough to predict PH in COPD patients.